PENCABUTAN HAK MEMILIH DAN DIPILIH DALAM JABATAN PUBLIK TERHADAP NARAPIDANA TINDAK PIDANA KORUPSI - Amrullah, Muhammad Salam (Jurnal Hukum Volkgeist, 2017)
Revocation of the right to vote and be elected in public office as an additional penalty applied to the defendant allows corruption cases. This research aimed (1) to investigate and analyze the relevance of the annulment of the vote right for the public position election of the corruption prisoners as seen from the perspective of the criminal aims; and (2) to investigate and analyze the factors effecting the annulment of the vote rights for the public positions  of the corruption prisoners. The research was conducted in Jakarta city by choosing the institutions relevant to the problem s of this thesis; they were the corruption eradication commission (KPK), Jakarta first thesis instance court, constitutional court, and the supreme court. The method used was the empirical study of the normative law. The nature of the research was descriptive using the primary and secondary data collected from the documents and interview techniques as well as reading the materials related to the exixting problems. The collected data were the analyzed using the qualitative descriptive analysis. The research result revealed that the imposition of the right to vote and to be voted for the public positions as the additional penalty was considered relevant to the purpose of the punishment,  I,e. to give retaliation and deterrent effect against the perpetrators of corruption. The law enforcement continued to expect that this additional punishment could prevent further corruption actions in the future. The factors effecting the implementation of the annulment of the right to vote and be voted for the public positions were already stated  clearly in the  law No. 31 of 1999 about the amendment of the criminal action corruption Jo the law  No. 20 of 2001 about the amendment of the law No. 31 of 1999 about the eradication of the corruption criminal  action, and the code of criminal law. As for its legal material, the conditions and mechanism of the annulment of the right to vote and be voted for public positions should be stated more clearly.